Conductive microsphere for anisotropic conductive film and preparation method thereof
Through the use of modified crosslinking agents and carboxylated chitin oligosaccharides and other raw materials, combined with ultrasonic spraying technology and electroless nickel plating process, conductive microspheres with high mechanical strength and conductive properties were prepared, which solved the problems of rebound and brittleness of existing conductive microspheres at high temperatures and improved the application performance of anisotropic conductive films.
Patent Information
- Application Number
- CN202510355983.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing conductive microspheres have rebound problems after heating and pressurization, resulting in a decrease in the contact area with metal contacts, reducing the conductivity of electronic products. At the same time, their coating uniformity and crushing strength are insufficient, limiting the application of anisotropic conductive films in high-end electronic devices.
Using modified crosslinking agents and carboxylated chitin oligosaccharides and other raw materials, conductive microspheres are prepared through ultrasonic spraying technology, and electroless nickel plating is carried out to form conductive microspheres with core-shell structures to improve their mechanical strength and conductive properties.
The mechanical strength and conductivity of the conductive microspheres are improved, the brittleness and risk of peeling of the coating are reduced, and the contact area and stability with metal contacts are enhanced, thereby improving the performance of the anisotropic conductive film.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive microspheres, and in particular to conductive microspheres for anisotropic conductive films and a preparation method thereof. Background Art
[0002] Anisotropic conductive film (ACF) is a material widely used in the field of electronic packaging. Its core is that it can conduct electricity in the vertical direction and insulate in the horizontal direction, thereby achieving high-precision electrical connections between electronic components. This material is usually composed of an insulating resin matrix and conductive microspheres dispersed in it. The conductive microspheres play a key role in this. They contact the upper and lower metal contacts under pressure and heating to form a conductive path. However, many conductive microspheres on the market currently have certain rebound problems after heating and pressurization, resulting in a decrease in the contact area with the metal contacts, thereby reducing the conductive performance of electronic products.
[0003] In addition, the coating uniformity, crushing strength and other properties of the conductive microspheres are also crucial to the conductive performance and reliability of the anisotropic conductive film. Although the existing common polymer microsphere chemical plating can achieve chemical plating of the metal coating, there is a problem of low interfacial bonding between the metal coating and the polymer microsphere core. During the compression process, the crushing strength of the conductive microspheres is weak and the metal layer is easy to fall off. These problems limit the application of anisotropic conductive films in high-end electronic devices. Therefore, the development of a conductive microsphere for anisotropic conductive film that can solve the above problems is of great significance to meet the demand for high-performance connection materials in modern electronic devices.
[0004] A Chinese invention patent with publication number CN109735257A discloses a heat-resistant conductive microsphere for anisotropic conductive adhesive film and a preparation method thereof. The method uses methyl methacrylate, methacrylic acid, and hexachlorocyclotriphosphazene as monomers, polyvinyl pyrrolidone as a dispersant, ethanol and water as solvents, and azobisisoheptylnitrile as an initiator. Monodispersed methyl methacrylate-methacrylic acid-hexachlorocyclotriphosphazene crosslinked copolymer microspheres are prepared by dispersion polymerization, and then roughening, sensitization, activation, and chemical nickel plating are performed to obtain heat-resistant conductive microspheres with a core-shell structure. Although the particle size distribution is uniform, the microspheres are easily broken and the coating uniformity is poor. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a conductive microsphere for anisotropic conductive film and a preparation method thereof.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions: A conductive microsphere for anisotropic conductive film, comprising the following raw materials in parts by weight: Styrene: 80-100 parts, initiator: 0.5-1.5 parts, modified cross-linking agent: 6-8 parts, dispersant: 2-8 parts, carbon nanotubes: 10-12 parts, graphene: 15-20 parts, deionized water: 80 parts, toluene: 800 parts; The modified crosslinking agent is prepared by the following method: S1: under nitrogen protection, toluene, 2,2'-diallyl bisphenol A and epichlorohydrin were added to the reactor, stirred, heated to 80-100°C, reacted for 2-4h, cooled to 60°C, slowly added sodium hydroxide solution dropwise, continued to react for 1-2h after addition, and post-treated to obtain intermediate 1; S2: DMF, intermediate 1 and γ-aminopropyltriethoxysilane are added into the reactor in sequence, stirred and mixed, heated to 80-120° C., reacted for 4-6 hours, and post-treated to obtain a modified cross-linking agent.
[0007] In step S1, the mass ratio of toluene, 2,2'-diallyl bisphenol A and epichlorohydrin is 30:(10-12):(5-7); In step S2, the mass ratio of DMF, intermediate 1 and γ-aminopropyltriethoxysilane is 50:(6-8):(5-7).
[0008] The initiator is one of azobisisobutyronitrile and ammonium persulfate.
[0009] The dispersant is one of polyethyleneimine, polyvinyl pyrrolidone and polyvinyl alcohol.
[0010] A method for preparing conductive microspheres for anisotropic conductive film comprises the following steps: S1: Weigh by weight: 80-100 parts of styrene, 0.5-1.5 parts of initiator, 6-8 parts of modified crosslinking agent, 2-8 parts of dispersant, 10-12 parts of carbon nanotubes, 15-20 parts of graphene, 80 parts of deionized water, and 800 parts of toluene; S2: Add toluene, styrene, initiator, and dispersant into the reactor, introduce nitrogen, heat to 80-100°C, perform polymerization for 10-16h, then slowly dropwise add modified crosslinking agent, continue the reaction for 6-8h, and obtain mixed solution A; S3: adding carbon nanotubes and graphene into deionized water, ultrasonically mixing to obtain a mixed solution B, slowly adding the mixed solution A into the mixed solution B, stirring and mixing to obtain a precursor solution, atomizing the precursor solution through an ultrasonic spray device and spraying it into a high-temperature furnace, staying for 4-6 hours, to form precursor microspheres; S4: Disperse the precursor microspheres in the nickel plating solution, stir and sonicate, control the temperature at 75-80°C and pH = 4.5-5.0, complete chemical plating, filter, wash and dry to obtain conductive microspheres for anisotropic conductive film.
[0011] The nickel plating solution has a nickel salt concentration of 10-30 g / L, a complexing agent concentration of 10-15 g / L, and a reducing agent concentration of 15-20 g / L.
[0012] The nickel salt is nickel sulfate, and the reducing agent is sodium hypophosphite.
[0013] The complexing agent is carboxylated chitosan oligosaccharide, and the carboxylated chitosan oligosaccharide is prepared by the following method: Dissolve 10g of chitosan oligosaccharide in 1000mL of deionized water and cool to 0-5°C in an ice bath; add 1g of NaBr and 0.16g of TEMPO in sequence with stirring, and slowly add 100mL of NaClO solution; at the same time, adjust the pH to 10.0-10.5 with 1M NaOH solution, react for 2h, add 100mL of anhydrous ethanol to quench the reaction, and stir for 10min; adjust the solution to neutral with 0.1M HCl; transfer the reaction solution to a dialysis bag, dialyze with deionized water for 48h, and freeze-dry the dialyzate to obtain carboxylated chitosan oligosaccharide.
[0014] Due to the adoption of the above technical solution, the beneficial effects of the present invention include: (1) The present invention firstly synthesizes intermediate 1 by reacting the hydroxyl group in 2,2'-diallyl bisphenol A with the chlorine atom in epichlorohydrin, and then the epoxy group in intermediate 1 reacts with the amino group in γ-aminopropyltriethoxysilane to prepare a modified crosslinking agent.
[0015] (2) In the present invention, in the presence of NaBr and NaClO, TEMPO is oxidized to generate highly active oxoammonium cations (TEMPO + ), selectively oxidizing the primary hydroxyl group (-CH2OH) at the C6 position of chitosan oligosaccharide to generate an aldehyde intermediate (-CHO), which is then further oxidized to a carboxylic acid group (-COOH) by NaClO under alkaline conditions (pH 10.0-10.5). Ethanol terminates the reaction by reducing the residual oxidant, and finally the salt byproducts are removed by dialysis and freeze-dried to obtain carboxylated chitosan oligosaccharide. The key to this reaction is the high selectivity of the TEMPO system for primary hydroxyl groups, while amino and secondary hydroxyl groups are basically unaffected.
[0016] (3) The modified crosslinker prepared by the present invention has 2,2'-diallyl bisphenol A as the core structure. Its bisphenol A group has high thermal stability (decomposition temperature> 200°C), which can withstand the high temperature (130-180°C) in the hot pressing process of anisotropic conductive film (ACF), avoiding the performance degradation caused by the degradation of the crosslinker. The introduced γ-aminopropyltriethoxysilane generates silanol groups through hydrolysis, forming stable chemical bonds with the conductive microspheres or resin matrix, greatly improving the interfacial adhesion and avoiding the shedding of conductive particles.
[0017] (4) Carboxylated chitosan oligosaccharides contain a large number of carboxyl groups, which can provide more active sites and higher reactivity. These carboxyl groups can form stable complexes with metal ions; the amino and hydroxyl groups of chitosan oligosaccharides can also participate in the complexation reaction, thereby significantly improving the complexing ability of the complexing agent. This enhanced complexing ability can better fix and disperse the conductive microspheres and improve the performance of the conductive film.
[0018] (5) The present invention utilizes ultrasonic spray technology to atomize the precursor solution into uniform droplets through high-frequency vibration. The droplets rapidly dehydrate and shrink in a high-temperature furnace to form a wrinkled surface. The wrinkled structure disperses stress through the surface concave-convex morphology, thereby improving the mechanical ability of the microspheres. DETAILED DESCRIPTION
[0019] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.
[0020] Example 1 Preparation of modified cross-linking agent: S1: Under nitrogen protection, add 300g toluene, 100g 2,2'-diallyl bisphenol A, and 50g epichlorohydrin to the reactor, stir, heat to 80℃, react for 4h, cool to 60℃, slowly drop 40g 48wt% sodium hydroxide solution, drop for 20min, continue to react for 2h after drop, cool to room temperature after the reaction, slowly add 1M dilute hydrochloric acid solution until the pH value of the reaction solution is neutral. Stand and separate, separate the water phase, retain the organic phase, distill under reduced pressure at 70℃ for 2h, then add 50ml saturated sodium chloride solution for washing, repeat three times, and vacuum dry at 70℃ for 3h to obtain intermediate 1; S2: 500g DMF, 60g intermediate 1 and 50g γ-aminopropyltriethoxysilane were added to the reactor in sequence, stirred and mixed, heated to 80°C, reacted for 6h, cooled to room temperature, and distilled at 60°C under reduced pressure for 4h, then added with 500ml ethyl acetate for extraction, repeated three times, then added with 50g anhydrous magnesium sulfate for drying for 5h, filtered, and separated by column chromatography to obtain a modified cross-linking agent, the structural formula of which is as follows:
[0021] Its nuclear magnetic resonance hydrogen spectrum data are as follows: 1 H NMR (500 MHz, Chloroform-d) δ 7.16 – 7.01 (m, 4H), 6.74 (d, J =7.6 Hz, 2H), 5.87 (ddt, J = 16.8, 10.1, 6.7 Hz, 2H), 5.27 – 4.87 (m, 4H),4.77 (tt, J = 6.6, 4.5 Hz, 2H), 4.11 (dd, J = 12.3, 5.2 Hz, 2H), 3.97 (d, J =5.7 Hz, 2H), 3.95 – 3.69 (m, 16H), 3.29 (dtd, J = 6.7, 1.5, 0.8 Hz, 4H), 2.96(ddd, J = 13.2, 6.5, 4.9 Hz, 2H), 2.70 (dqd, J = 8.5, 6.8, 4.7 Hz, 6H), 1.74– 1.46 (m, 10H), 1.21 (t, J = 7.4 Hz, 18H), 0.71 (t, J = 9.1 Hz, 4H).
[0022] Example 2 Preparation of modified crosslinking agent: S1: Under nitrogen protection, add 300g toluene, 110g 2,2'-diallyl bisphenol A, and 60g epichlorohydrin to the reactor, stir, heat to 90℃, react for 3h, cool to 60℃, slowly drop 45g 48wt% sodium hydroxide solution, drop for 20min, continue to react for 1.5h, cool to room temperature after the reaction, slowly add 1M dilute hydrochloric acid solution until the pH value of the reaction solution is neutral. Let stand to separate, separate the water phase, retain the organic phase, distill under reduced pressure at 60℃ for 3h, then add 50ml saturated sodium chloride solution for washing, repeat three times, and vacuum dry at 60℃ for 4h to obtain intermediate 1; S2: 500g DMF, 70g intermediate 1 and 60g γ-aminopropyltriethoxysilane were added to the reactor in sequence, stirred and mixed, heated to 100°C, reacted for 5h, cooled to room temperature, and distilled at 70°C under reduced pressure for 3h, then added with 500ml ethyl acetate for extraction, repeated three times, then added with 50g anhydrous magnesium sulfate for drying for 5h, filtered, and separated by column chromatography to obtain the modified cross-linking agent.
[0023] Example 3 Preparation of modified cross-linking agent: S1: Under nitrogen protection, add 300g toluene, 120g 2,2'-diallyl bisphenol A, and 70g epichlorohydrin to the reactor, stir, heat to 100℃, react for 2h, cool to 60℃, slowly drop 50g 48wt% sodium hydroxide solution, drop for 20min, continue to react for 1h after the drop, cool to room temperature after the reaction, slowly add 1M dilute hydrochloric acid solution until the pH value of the reaction solution is neutral. Stand and separate, separate the water phase, retain the organic phase, distill under reduced pressure at 50℃ for 4h, then add 50ml saturated sodium chloride solution for washing, repeat three times, and vacuum dry at 50℃ for 5h to obtain intermediate 1; S2: 500g DMF, 80g intermediate 1 and 70g γ-aminopropyltriethoxysilane were added to the reactor in sequence, stirred and mixed, heated to 120°C, reacted for 4h, cooled to room temperature, and distilled at 80°C under reduced pressure for 2h, then added with 500ml ethyl acetate for extraction, repeated three times, then added with 50g anhydrous magnesium sulfate for drying for 5h, filtered, and separated by column chromatography to obtain the modified cross-linking agent.
[0024] Example 4 Preparation of carboxylated chitosan oligosaccharide Dissolve 10g of chitosan oligosaccharide in 500mL of deionized water and cool to 0-5°C in an ice bath; add 1g of NaBr and 0.16g of TEMPO in sequence and stir for 10min to form an activation system; slowly add 100mL of NaClO solution (take 10mL of sodium hypochlorite stock solution (10wt%) and dilute it to 100mL with deionized water) at a drop rate of 5mL / min; at the same time, adjust the pH to 10.0-10.5 with 1M NaOH solution, react for 2h, add 80mL of anhydrous ethanol to quench the reaction, and stir for 10min; adjust the solution pH to 7.0 with 0.1M HCl to avoid protonation of carboxylic acid; transfer the reaction solution to a dialysis bag (MWCO 1000Da), dialyze with deionized water for 48h (change water every 8h), and freeze (-50°C) and dry the dialyzate for 48h to obtain white powdery carboxylated chitosan oligosaccharide.
[0025] Example 5 Preparation of conductive microspheres for anisotropic conductive film: S1: Weigh by weight: styrene: 800 g, initiator (azobisisobutyronitrile): 5 g, modified cross-linking agent (prepared in Example 1): 60 g, dispersant (polyethyleneimine): 20 g, carbon nanotubes: 100 g, graphene: 150 g, deionized water: 800 g, toluene: 8000 g; S2: Add toluene, styrene, initiator, and dispersant to the reactor, stir, introduce nitrogen, heat to 80°C, and polymerize for 16 hours. Then slowly drop the modified crosslinking agent for 10 minutes, continue the reaction for 8 hours, and cool to room temperature to obtain a mixed solution A. S3: Add carbon nanotubes and graphene into deionized water, mix them by ultrasonic for 10 minutes to obtain a mixed solution B, slowly add the mixed solution A into the mixed solution B, stir and mix them to obtain a precursor solution, atomize the precursor solution by an ultrasonic spray device (ultrasonic frequency is 120kHz), and then spray it into a high-temperature furnace at 220°C for 6 hours to form precursor microspheres; S4: The precursor microspheres are chemically plated, and the precursor microspheres are dispersed in 1000 ml of nickel plating solution (10 g / L nickel sulfate, 10 g / L complexing agent (prepared in Example 4), and 15 g / L sodium hypophosphite), stirred at 150 rpm, ultrasonically dispersed at 75 kHz for 1 hour, controlled at 75-80°C, pH = 4.5-5.0, filtered, washed with 1000 ml of anhydrous ethanol, and vacuum dried at 70°C for 5 hours to obtain conductive microspheres for anisotropic conductive film.
[0026] Example 6 Preparation of conductive microspheres for anisotropic conductive film: S1: Weigh by weight: styrene: 900 g, initiator (ammonium persulfate): 10 g, modified cross-linking agent (prepared in Example 2): 70 g, dispersant (polyvinyl pyrrolidone PVP K25): 50 g, carbon nanotubes: 110 g, graphene: 180 g, deionized water: 800 g, toluene: 8000 g; S2: Add toluene, styrene, initiator, and dispersant to the reactor, stir, introduce nitrogen, heat to 90°C, and polymerize for 13 hours. Then slowly drop the modified crosslinking agent for 15 minutes, continue the reaction for 7 hours, and cool to room temperature to obtain a mixed solution A. S3: Add carbon nanotubes and graphene into deionized water, mix them by ultrasonic for 10 minutes to obtain a mixed solution B, slowly add the mixed solution A into the mixed solution B, stir and mix them to obtain a precursor solution, atomize the precursor solution by an ultrasonic spray device (ultrasonic frequency is 120kHz), and then spray it into a high-temperature furnace at 220°C for 5 hours to form precursor microspheres; S4: The precursor microspheres are chemically plated, and the precursor microspheres are dispersed in 1000 ml of nickel plating solution (15 g / L nickel sulfate, 15 g / L complexing agent (prepared in Example 4), and 18 g / L sodium hypophosphite), stirred at 150 rpm, ultrasonically dispersed at 75 kHz for 1 hour, controlled at 75-80°C, pH = 4.5-5.0, filtered, washed with 1000 ml of anhydrous ethanol, and vacuum dried at 70°C for 5 hours to obtain conductive microspheres for anisotropic conductive film.
[0027] Example 7 Preparation of conductive microspheres for anisotropic conductive film: S1: Weigh by weight: styrene: 1000 g, initiator (ammonium persulfate): 15 g, modified cross-linking agent (prepared in Example 3): 80 g, dispersant (polyvinyl alcohol PVA-2499): 80 g, carbon nanotubes: 120 g, graphene: 200 g, deionized water: 800 g, toluene: 8000 g; S2: Add toluene, styrene, initiator, and dispersant into the reactor, stir, introduce nitrogen, heat to 100°C, perform polymerization for 10 hours, then slowly drop the modified crosslinking agent for 20 minutes, continue the reaction for 6 hours, cool to room temperature, and obtain a mixed solution A; S3: Add carbon nanotubes and graphene into deionized water, mix them by ultrasonic for 10 minutes to obtain a mixed solution B, slowly add the mixed solution A into the mixed solution B, stir and mix them to obtain a precursor solution, atomize the precursor solution by an ultrasonic spray device (ultrasonic frequency is 120kHz), and then spray it into a high-temperature furnace at 220°C for 4 hours to form precursor microspheres; S4: The precursor microspheres are chemically plated, and the precursor microspheres are dispersed in 1000 ml of nickel plating solution (30 g / L nickel sulfate, 15 g / L complexing agent (prepared in Example 4), 20 mg / L sodium hypophosphite), stirred at 150 rpm, ultrasonically dispersed at 75 kHz for 1 hour, controlled at 75-80°C, pH = 4.5-5.0, filtered, washed with 1000 ml of anhydrous ethanol, and vacuum dried at 70°C for 5 hours to obtain conductive microspheres for anisotropic conductive film.
[0028] When performing chemical plating in the examples and comparative examples of the present application, the pH is controlled within a specified range by using 0.1 M dilute sulfuric acid or 0.1 M sodium hydroxide.
[0029] Comparative Example 1 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the modified cross-linking agent is replaced by an equal weight of divinylbenzene.
[0030] Comparative Example 2 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the modified cross-linking agent is replaced by an equal weight of the intermediate 1 prepared in step S1 of Example 2.
[0031] Comparative Example 3 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the modified cross-linking agent is replaced by an equal weight of vinyltriethoxysilane.
[0032] Comparative Example 4 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the modified cross-linking agent is replaced by an equal weight of a modified cross-linking agent prepared by the following method: S1: Under nitrogen protection, add 300g toluene, 110g 2-allyl-4-methylphenol, and 60g epichlorohydrin to the reactor, stir, heat to 90℃, react for 3h, cool to 60℃, slowly drop 45g 48wt% sodium hydroxide solution, drop for 20min, continue to react for 1.5h, cool to room temperature after the reaction, slowly add 1M dilute hydrochloric acid solution until the pH value of the reaction solution is neutral. Stand and separate, separate the water phase, retain the organic phase, distill under reduced pressure at 60℃ for 3h, then add 50ml saturated sodium chloride solution for washing, repeat three times, and vacuum dry at 60℃ for 4h to obtain intermediate 1; S2: 500g DMF, 70g intermediate 1 and 60g γ-aminopropyltriethoxysilane were added to the reactor in sequence, stirred and mixed, heated to 100°C, reacted for 5h, cooled to room temperature, and distilled at 70°C under reduced pressure for 3h, then added with 500ml ethyl acetate for extraction, repeated three times, then added with 50g anhydrous magnesium sulfate for drying for 5h, filtered, and separated by column chromatography to obtain the modified cross-linking agent.
[0033] Comparative Example 5 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference is that the complexing agent in the nickel plating solution is replaced by EDTA of equal concentration.
[0034] Comparative Example 6 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference is that the complexing agent in the nickel plating solution is replaced by unmodified chitosan oligosaccharide of equal concentration.
[0035] Comparative Example 7 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the complexing agent in the nickel plating solution is replaced with a complexing agent prepared by the following method with equal concentration: Ultrasonic dispersion of 10g chitosan in 500mL deionized water, cooling to 0-5℃ in an ice bath; sequentially add 1g NaBr and 0.16g TEMPO and stir for 10min to form an activation system; slowly drop 100mL NaClO solution (take 10mL sodium hypochlorite stock solution (containing 10wt% effective chlorine), dilute to 100mL with deionized water), the drop rate is 5mL / min; at the same time, adjust the pH to 10.0-10.5 with 1M NaOH solution, react for 2h, add 80mL anhydrous ethanol to quench the reaction, and stir for 10min; adjust the solution to pH=7.0 with 0.1M HCl to produce precipitation; filter, and dry at 50℃ for 5h to obtain carboxylated chitosan.
[0036] Comparative Example 8 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the complexing agent in the nickel plating solution is replaced with a complexing agent prepared by the following method with equal concentration: Dissolve 10 g of chitosan oligosaccharide in 500 mL of deionized water, stir until completely dissolved, add 10 mL of concentrated sulfuric acid to adjust the pH to 1.5-2.0 to form an acidic reaction system; add 5 g of potassium permanganate to the solution in batches (1 g per batch, 3 min interval between batches), control the temperature at 45 ° C, stir the reaction for 6 hours, add 80 mL of anhydrous ethanol to quench the reaction, and stir for 10 minutes; filter to remove the generated manganese dioxide (MnO2) precipitate, and adjust the pH of the filtrate to neutral 7 with 5% NaOH solution; transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 1000 Da, dialyze with deionized water for 48 hours, and replace the dialysate every 8 hours. After dialysis, the solution was pre-frozen at -50 ° C and dried in a freeze dryer for 48 hours to obtain white powdered carboxylated chitosan oligosaccharide.
[0037] Comparative Example 9 A conductive microsphere for anisotropic conductive film, the raw material composition and process are basically the same as those of Example 6, the difference being that the complexing agent in the nickel plating solution is replaced with a complexing agent prepared by the following method with equal concentration: Dissolve 10g of chitosan oligosaccharide (deacetylation degree ≥90%, molecular weight 3000Da) in 500mL of deionized water and cool to 0-5℃ in an ice bath; add 1g of NaBr and 0.16g of TEMPO in sequence and stir for 10min to form an activation system; slowly add 100mL of NaClO solution (take 10mL of sodium hypochlorite stock solution (10wt%) and dilute it to 100mL with deionized water) at a drop rate of 5mL / min; at the same time, adjust the pH to 10.0-10.5 with 1M NaOH solution, react for 2h, add 80mL of anhydrous ethanol to quench the reaction, and stir for 10min; adjust the solution to pH=7.0 with 0.1M HCl to avoid protonation of carboxylic acid; transfer the reaction solution to a dialysis bag (MWCO 1000Da), dialyze with deionized water for 48h (change water every 8h), and freeze (-50℃) and dry the dialysate for 24h to obtain white powdery carboxylated chitosan oligosaccharide.
[0038] Comparative Example 10 A heat-resistant conductive microsphere for anisotropic conductive adhesive film is prepared by using the raw material composition, proportion and method of Example 1 of the Chinese invention patent with publication number CN109735257A.
[0039] Unless otherwise specified, the materials used in the examples and comparative examples of this application are as follows: The molecular weight of polyethyleneimine is Mn=10000; chitosan oligosaccharide is produced by Zhejiang Jinke Pharmaceutical Co., Ltd., with a purity of 99%, a deacetylation degree of ≥90%, and a molecular weight of 2000Da; chitosan is produced by Zhejiang Jinke Pharmaceutical Co., Ltd., with a purity of 99% and an average molecular weight of 25,000 Daltons; the carbon nanotube model is: FT900, with a tube diameter of 10-25nm and a purity of 99.9%, purchased from Jiangsu Tiannai Technology Co., Ltd.; the graphene model is LB1G3-54, purchased from Jiangsu Tiannai Technology Co., Ltd. The ultrasonic spray device used in this application is the UAM4000L spray device of Hangzhou Chifei Ultrasonic Equipment Co., Ltd.
[0040] The volume resistivity of the anisotropic conductive films prepared in Examples 5-7 and Comparative Examples 1-10 was tested using conductive microspheres, and the experimental method was carried out in accordance with GB / T 1410-2006 "Determination of volume resistivity and surface resistivity of solid insulating materials"; the hardness of the anisotropic conductive films prepared in Examples 5-7 and Comparative Examples 1-10 was tested using conductive microspheres, and the experimental method was carried out in accordance with GB / T 4340.1-2009 "Metal Vickers hardness test Part 1: Test method"; the particle size distribution was tested using a Malvern dynamic light scattering instrument and the average particle size and coefficient of variation CV were calculated. The test results are shown in Table 1.
[0041] Table 1
[0042] It can be seen from Table 1 that the coefficient of variation of the particle size of the conductive microspheres for the anisotropic conductive films prepared in Examples 5, 6, and 7 is less than 2.3%, and the volume resistivity is less than 2.5×10 -3 Ω·cm, K value is greater than 350kgf / mm 2 , with excellent conductivity and hardness.
[0043] The modified crosslinking agent added in Comparative Example 1 is divinylbenzene in an equal weight. From the data in Table 1, it can be seen that the volume resistivity is 5.0×10 -3 Ω·cm, K value is 250kgf / mm 2 , poor conductivity and low hardness, which is due to the high double bond crosslinking density of divinylbenzene, which is easy to form a rigid network, which may increase the brittleness of the prepared conductive microspheres. The crosslinking agent of the present invention can form a moderate crosslinking network through the synergistic effect of allyl and silane groups, and can also relieve stress through the flexibility of siloxane bonds, making the conductive microspheres not easy to break.
[0044] Comparative Example 2 is different from Example 6 in that γ-aminopropyltriethoxysilane is not grafted in the added cross-linking agent. It can be seen from the data in Table 1 that the conductivity is poor and the hardness is low. This is because the cross-linking agent without silane grafting leads to insufficient cross-linking degree, which makes the microspheres easy to deform at high temperatures; at the same time, silane is not grafted, the microspheres are easy to agglomerate, and the dispersion performance is poor, resulting in stress concentration inside the microspheres, reducing the mechanical and conductive properties of the conductive microspheres.
[0045] Comparative Example 3 is different from Example 6 in that the added modified cross-linking agent is replaced by vinyl triethoxysilane. It can be seen from the data in Table 1 that the conductivity is poor and the hardness is low. This is because the rigid bisphenol A skeleton of 2,2'-diallyl bisphenol A can provide high cross-linking density and thermal stability, and its allyl double bonds can copolymerize with styrene to form a stable three-dimensional cross-linked network, thereby improving the performance of the conductive microspheres.
[0046] Comparative Example 4 is different from Example 6 in that the 2,2'-diallyl bisphenol A in step S1 is replaced by 2-allyl-4-methylphenol in the preparation process of the modified crosslinking agent. It can be seen from the data in Table 1 that the volume resistivity is 3.2×10 -3 Ω·cm, K value is 320kgf / mm 2 , poor conductivity, low hardness, 2-allyl-4-methylphenol has a relatively simple structure, and the cross-linking network of the monophenol structure is weak, which leads to a decrease in the mechanical strength of the conductive microspheres. The rigidity of the 2,2'-diallyl bisphenol A structure helps to improve the toughness of the material, while the structure of 2-allyl-4-methylphenol may cause the toughness of the material to deteriorate and be prone to brittle fracture.
[0047] Comparative Example 5 is different from Example 6 in that the complexing agent is replaced by EDTA. From the data in Table 1, it can be seen that the volume resistivity is 4.3×10 -3 Ω·cm, K value is 310kgf / mm 2 The complexing agent prepared by the invention has a large number of carboxyl groups, can provide more complexing sites, and can significantly improve the complexing ability.
[0048] Comparative Examples 6, 7, 8, and 9 are respectively prepared by replacing the complexing agent with unmodified chitosan oligosaccharide, carboxylated chitosan, carboxylated chitosan oligosaccharide prepared by potassium permanganate oxidation, and carboxylated high molecular weight chitosan oligosaccharide. It can be seen from Table 1 that their hardness and conductive properties are not as good as those prepared in Example 1. The reasons are analyzed as follows: Uncarboxylated chitosan oligosaccharide lacks strong coordination groups (containing only hydroxyl and amino groups) and has a weak complexing ability for nickel ions, resulting in the free Ni in the plating solution. 2+ The concentration increases; this causes the coating to coarsen, the porosity increases, and the resistivity increases. At the same time, the lack of carboxylic acid groups in the pH buffering capacity will lead to a decrease in the reduction efficiency of sodium hypophosphite. The long molecular chain of carboxylated chitosan will form a dense adsorption layer on the surface of the microspheres, covering a large active site, which will hinder the Ni 2+ The interface reduction of the nickel ions hinders the uniform deposition of nickel ions. In addition, the dissociation rate of the complex is low, the nickel release is insufficient, and the nickel distribution of the coating is gradient, which leads to a significant deterioration of the bonding strength and conductivity uniformity of the coating. The strong oxidizing property of potassium permanganate leads to the breakage of the chitosan oligosaccharide molecular chain and the uneven distribution of the carboxylic acid groups, which reduces the effective complexation sites and may introduce Mn 2+ Impurities, which are related to Ni 2+ Competitive adsorption forms a non-conductive NiMnO3 impurity phase, destroying the continuity of the coating, resulting in a significant decrease in conductivity and hardness. Carboxylated high molecular weight chitosan oligosaccharides are prone to form micelles to encapsulate nickel ions due to their long molecular chains, and their complexes have high thermodynamic stability. They have poor ability to dissociate and release Ni ions at a process temperature of 75-80°C, resulting in a significant decrease in the density and deposition rate of the coating, so its hardness and conductivity are reduced simultaneously.
[0049] Comparative Example 10 is a heat-resistant conductive microsphere for anisotropic conductive film prepared by using the raw material composition, ratio and method of Example 1 of the Chinese invention patent with publication number CN109735257A. It can be seen from the data in Table 1 that the volume resistivity is 5.6×10 -3 Ω·cm, K value is 230kgf / mm 2 , poor conductivity.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A conductive microsphere for anisotropic conductive film, characterized in that: The invention comprises the following raw materials in parts by weight: Styrene: 80-100 parts, initiator: 0.5-1.5 parts, modified cross-linking agent: 6-8 parts, dispersant: 2-8 parts, carbon nanotubes: 10-12 parts, graphene: 15-20 parts, deionized water: 80 parts, toluene: 800 parts; The modified crosslinking agent is prepared by the following method: S1: under nitrogen protection, toluene, 2,2'-diallyl bisphenol A and epichlorohydrin were added to the reactor, stirred, heated to 80-100°C, reacted for 2-4h, cooled to 60°C, slowly added sodium hydroxide solution dropwise, continued to react for 1-2h after addition, and post-treated to obtain intermediate 1; S2: DMF, intermediate 1 and γ-aminopropyltriethoxysilane are added into the reactor in sequence, stirred and mixed, heated to 80-120° C., reacted for 4-6 hours, and post-treated to obtain a modified cross-linking agent.
2. The conductive microsphere for anisotropic conductive film according to claim 1, characterized in that: In step S1, the mass ratio of toluene, 2,2'-diallyl bisphenol A and epichlorohydrin is 30:(10-12):(5-7); In step S2, the feed mass ratio of DMF, intermediate 1 and γ-aminopropyltriethoxysilane is 50:(6-8):(5-7).
3. The conductive microsphere for anisotropic conductive film according to claim 1, characterized in that: The initiator is one of azobisisobutyronitrile and ammonium persulfate.
4. The conductive microsphere for anisotropic conductive film according to claim 1, characterized in that: The dispersant is one of polyethyleneimine, polyvinyl pyrrolidone and polyvinyl alcohol.
5. A method for preparing conductive microspheres for anisotropic conductive film according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Weigh by weight: 80-100 parts of styrene, 0.5-1.5 parts of initiator, 6-8 parts of modified crosslinking agent, 2-8 parts of dispersant, 10-12 parts of carbon nanotubes, 15-20 parts of graphene, 80 parts of deionized water, and 800 parts of toluene; S2: Add toluene, styrene, initiator, and dispersant into the reactor, introduce nitrogen, heat to 80-100°C, perform polymerization for 10-16h, then slowly dropwise add modified crosslinking agent, continue the reaction for 6-8h, and obtain mixed solution A; S3: adding carbon nanotubes and graphene into deionized water, ultrasonically mixing to obtain a mixed solution B, slowly adding the mixed solution A into the mixed solution B, stirring and mixing to obtain a precursor solution, atomizing the precursor solution through an ultrasonic spray device and spraying it into a high-temperature furnace, staying for 4-6 hours, to form precursor microspheres; S4: Disperse the precursor microspheres in the nickel plating solution, stir and sonicate, control the temperature at 75-80°C and pH = 4.5-5.0, complete chemical plating, filter, wash and dry to obtain conductive microspheres for anisotropic conductive film.
6. The preparation method according to claim 5, characterized in that: The nickel plating solution has a nickel salt concentration of 10-30 g / L, a complexing agent concentration of 10-15 g / L, and a reducing agent concentration of 15-20 g / L.
7. The preparation method according to claim 6, characterized in that: The nickel salt is nickel sulfate, and the reducing agent is sodium hypophosphite.
8. The preparation method according to claim 6, characterized in that: The complexing agent is carboxylated chitosan oligosaccharide, and the carboxylated chitosan oligosaccharide is prepared by the following method: Dissolve 10g of chitosan oligosaccharide in 500mL of deionized water and cool to 0-5°C in an ice bath; add 1g of NaBr and 0.16g of TEMPO in sequence with stirring, and slowly add 100mL of NaClO solution; at the same time, adjust the pH to 10.0-10.5 with 1M NaOH solution, react for 2h, add 100mL of anhydrous ethanol to quench the reaction, and stir for 10min; adjust the solution to neutral with 0.1M HCl; transfer the reaction solution to a dialysis bag, dialyze with deionized water for 48h, and freeze-dry the dialyzate to obtain carboxylated chitosan oligosaccharide.
Citation Information
Patent Citations
Heat-resisting conductive microsphere for anisotropic conductive adhesive film and preparation method
CN109735257A
Diallyl bisphenol A diglycidyl ether and preparation process and application thereof
CN105968070A
Method for preparing macromolecule microspheres based on high-voltage electrostatic ultrasonic atomization
CN107115830A
Synthesis method of micron-sized polystyrene microspheres
CN112724295A
Water-soluble organosilicon resin and application thereof
WO2018001100A1